Managing preschool teaching and learning activities in preschool: teachers, headmasters and parents perspectives in Kanowit district / Elia Hasimi - Hasimi, Elia (2013)
This study is conducted to investigate various perspectives among teachers, headmasters and parents regarding children development in social and interpersonal skills, communication skills, emerging mathematical skills, emerging literacy skills, large and small motor skills and emerging ndependence. Apart from that, the study is showing preschool teachers' performance in managing teaching and learning activities. This study is important to see if there is any relationship between children's development with preschool teachers' performance. Therefore, frequencies, descriptive analysis and correlation coefficient are used to analyze the data. The results show positive respond by high score of mean and standard deviation in children development and also preschool teacher performance. The other results indicated good performance of preschool teachers towards children development by significant value is p< .001, two-tailed.